2022
DOI: 10.3390/polym14183921
|View full text |Cite
|
Sign up to set email alerts
|

Generation of One-Dimensional Fibrous Polyethylene Nanocrystals in Epoxy Thermosets

Abstract: The one-dimensional (1D) polyethylene (PE) nanocrystals were generated in epoxy thermosets via crystallization-driven self-assembly. Toward this end, an ABA triblock copolymer composed of PE midblock and poly(ε-caprolactone) (PCL) endblocks was synthesized via the ring opening metathesis polymerization followed by hydrogenation approach. The nanostructured thermosets were obtained via a two-step curing approach, i.e., the samples were cured first at 80 °C and then at 150 °C. Under this condition, the one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Analogously, polystyrene- b -polycaprolactone (PS- b -PCL) with 2 : 1 ratio between blocks (1.8 : 1 strictly) forms crystalline PCL nanoribbons in a polystyrene matrix. 3 In this case, a miscible block with almost twice the volume of the immiscible block managed to stabilize the developed crystalline micelles. There are more examples in the literature showing different stability ratios according to the employed formulation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Analogously, polystyrene- b -polycaprolactone (PS- b -PCL) with 2 : 1 ratio between blocks (1.8 : 1 strictly) forms crystalline PCL nanoribbons in a polystyrene matrix. 3 In this case, a miscible block with almost twice the volume of the immiscible block managed to stabilize the developed crystalline micelles. There are more examples in the literature showing different stability ratios according to the employed formulation.…”
Section: Resultsmentioning
confidence: 95%
“…1 Particularly, 1D nanostructures formed by a semicrystalline polymeric phase are a promising choice, as they possess a range of remarkable properties related to their crystalline nature and high aspect ratio. 2,3 In this context, it was already demonstrated that it is possible to access to 1D semicrystalline nanostructures in a polymer matrix through the self-assembly of an amphiphilic block copolymer (BCP) in the reaction precursors [3][4][5][6] or by its reaction-induced microphase separation (RIMPS). 7,8 In the latter approach, both blocks of the BCP are initially soluble in the reactive solvent, but one of them becomes insoluble during matrix polymerization generating self-assembled nanophases (micelles).…”
Section: Introductionmentioning
confidence: 99%